Cryptography With One-Time Pad (OTP) Algorithm Xor Based - Reymond, Reymond; Johanes Manullang; Jhoische Tamba; Farel Parasian Sitohang; Eikel Nioisha Ginting (SEAN Institute, 2024)
The One-Time Pad (OTP) algorithm is a symmetric cryptographic method that is recognized as one of the most secure methods for encrypting data. In this study, OTP utilizes a unique random key that has the same length as the original message (plaintext). The encryption and decryption processes are carried out using the XOR (Exclusive OR) operation, which ensures that the resulting ciphertext does not provide information about the plaintext without knowing the key used. This document explains the basic theory of OTP, including the encryption process that produces ciphertext from plaintext and key, and the decryption process that returns ciphertext to plaintext. Through a manual example, this document shows how the characters in the plaintext and key are converted into binary format and operated with XOR to produce ciphertext. Testing using Python is also explained to provide a practical overview of the implementation of this algorithm. Although OTP offers a high level of security due to the random and disposable nature of the key, challenges in key distribution and management often limit its use in practice. The conclusion of this study confirms that although OTP is secure in theory, its real-world application requires special attention to key management to maintain data integrity and confidentiality.